Mayaya rising : Black female icons in Latin American and Caribbean literature and culture - Duke, Dawn, 1965- (Lewisburg, PA : Bucknell University Press, 2023)
"Who are the Black heroines of Latin America and the Caribbean? Where do we turn for models of transcendence among women of African ancestry in the region? In answer to the historical dearth of such exemplars, Mayaya Rising explores and celebrates the work of writers who intentionally center powerful female cultural archetypes. In this inventive analysis, Duke proposes three case studies and a corresponding womanist methodology through which to study and rediscover these figures. The musical Cuban-Dominican sisters and former slaves Teodora and Micaela Ginés inspired Aida Cartagena Portalatin's epic poem Yania tierra; the Nicaraguan matriarch of the May Pole, "Miss Lizzie," figures prominently in four anthologies from the country's Bluefields region; and the iconic palenqueras of Cartagena, Colombia are magnified in the work of poets María Teresa Ramírez Neiva and Mirian Díaz Pérez. In elevating these figures and foregrounding these works, Duke restores and repairs the scholarly record"--
Introduction: The fundamentals of glory -- A Cuban/Dominican case study. Teodora and Micaela Ginés: myth or history? -- The invention of history through poetry: a Dominican initiative -- A Nicaraguan case study. Tracing the dance steps of a "British" subject: Miss Lizzie's palo de mayo -- From "Mayaya Las Im Key" to Creole women's writings -- A Colombian case study. Rituals of alegría and ponchera: the enterprising palenqueras -- Palenquera writings: a twenty-first Century movement.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 22, 2022).
JSTOR
Keywords: Women, Black, in literature; Latin American literature -- Women authors -- History and criticism; Latin American literature -- Black authors -- History and criticism; Caribbean literature -- Women authors -- History and criticism; Caribbean literature -- Black authors -- History and criticism; Latin America -- Civilization -- African influences; Caribbean Area -- Civilization -- African influences; Noires dans la littérature.; Littérature latino-américaine -- Auteurs noirs -- Histoire et critique; Littérature antillaise -- Auteurs noirs -- Histoire et critique; LITERARY CRITICISM -- General; LITERARY CRITICISM / General; Women, Black, in literature; Latin American literature -- Women authors; Latin American literature -- Black authors; Civilization -- African influences; Caribbean literature -- Women authors; Caribbean literature -- Black authors; Latin America; Caribbean Area; Cuban music, Black poets in the Spanish-speaking Americas, Escrevivência, son cubano, Palenquera, Palenque de San Basilio, Benkos Bioho, Negritude, Afro-Hispanic literatura, Black historical experience, kuagros, Lumbalú, Catalina Loango, Afro-Cuban, Teodora and Micaela Ginés, Elizabeth Forbes Brooks, Miss Lizzie, Afro-Latin American women writers, Black women writers in Latin America, Afro-Latino Literature and Culture, Mayaya, May Pole, palo de mayo, Bluefields, Nicaragua, Son de la Ma Teodora, Afro-Colombian, Afro-Cuban women, Afro-descendant, Afro-Dominican, Afro-Latin American women, Afro-Latina, Afronegrismo, Afro-Nicaraguan, Aida Cartagena Portalatín, Caribbean, Conceição Evaristo, Creole, Cuba, Débora Almeida, Dominican Republic, el son Cubano, feminist, Georgina Herrera, griot, Latin America, Mel Adun, memory, Miriam Alves, Mujerismo, Mulherismo, Orishas, Oshun, Portuguese, rodas de poesia, Rubiera Castillo, Santos Febres, Spanish, Spanish Caribbean, womanist, Yalodés, Yania tierra, Yemayá.; Electronic books; Literary criticism; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.